2019
DOI: 10.1002/cia2.12075
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of eczematous eruptions caused by everolimus

Abstract: Objective Everolimus, an inhibitor of the mammalian target of rapamycin, has been used in the treatment of several types of tumor. Erythematous maculopapular and acneiform rashes are the major dermatological adverse events associated with everolimus therapy, but we encountered two cases of eczematous eruption caused by everolimus. Method We assessed the clinical features and laboratory findings of the two cases. Results A 52‐year‐old woman and a 59‐year‐old man developed pruritic papules and erythema over thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…A recent study showed that serum TARC levels were correlated with blood eosinophil counts in Type 2‐mediated drug eruptions 4 . In addition, elevated serum TARC levels have been reported in association with eczematous drug eruptions secondary to everolimus 5 . Our case showed elevation of serum TARC levels after the oral challenge test with clonazepam.…”
Section: Figuresupporting
confidence: 56%
See 2 more Smart Citations
“…A recent study showed that serum TARC levels were correlated with blood eosinophil counts in Type 2‐mediated drug eruptions 4 . In addition, elevated serum TARC levels have been reported in association with eczematous drug eruptions secondary to everolimus 5 . Our case showed elevation of serum TARC levels after the oral challenge test with clonazepam.…”
Section: Figuresupporting
confidence: 56%
“…4 In addition, elevated serum TARC levels have been reported in association with eczematous drug eruptions secondary to everolimus. 5 Our case showed elevation of serum TARC levels after the oral challenge test with clonazepam. We also observed fluctuation of serum TARC levels in association with the clinical course of the eruption.…”
mentioning
confidence: 49%
See 1 more Smart Citation